Analytical performance of a multiplex real-time pcr assay using taqman probes for quantification of trypanosoma cruzi satellite dna in blood samples - Duffy, Tomás (2013)
Fil: Duffy, Tomas. Instituto de Investigación en Ingeniería Genética y Biología Molecular "Dr. Héctor N. Torres". Grupo de Biología Molecular de la Enfermedad de Chagas; Argentina.